2020
DOI: 10.21203/rs.3.rs-15467/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association between pelvic asymmetry and non-specific chronic low back pain as assessed by the Global Postural System.

Abstract: Background: Empirical evidence that demonstrates the relationship between pelvic asymmetry and non-specific chronic low back pain (NCLBP) is currently lacking. Objective: To establish the reliability of the Global Postural System (GPS) in assessing pelvic asymmetry and identify the association between pelvic asymmetry parameters and the occurrence of NCLBP in young adults. Design: A cross-sectional, regression study. Methods: People who aged between 18 and 30 and were diagnosed with NCLBP were recruited. Healt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Patients with CLBP have reduced pelvic stability compared to healthy individuals due to weakness and imbalance of abdominal and PFM, and decreased ability of proprioceptive re-positioning function of the pelvic segment [20,21]. In particular, it is known that the pelvis is the control point that most effectively affects gait ability, and if pelvic stability is decreased, it has a negative effect on gait as well [21]. The PFMs block the outside of the pelvis and support the structures inside the abdominal pelvic cavity [5].…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Patients with CLBP have reduced pelvic stability compared to healthy individuals due to weakness and imbalance of abdominal and PFM, and decreased ability of proprioceptive re-positioning function of the pelvic segment [20,21]. In particular, it is known that the pelvis is the control point that most effectively affects gait ability, and if pelvic stability is decreased, it has a negative effect on gait as well [21]. The PFMs block the outside of the pelvis and support the structures inside the abdominal pelvic cavity [5].…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…This cross-sectional study collected data on college students with and without CNP. The GPS Lab, a professional and reliable assessment tool [21] , was used to measure posture.…”
Section: Methodsmentioning
confidence: 99%
“…is study recruited young adults with cNLBP as a published study indicated the prevalence of LBP among the young adult population is on the rise [20]. Identifying the relationship between APAs/ CPAs and pain level/disability may assist the early prevention or intervention of cNLBP [21].…”
Section: Sample Populationmentioning
confidence: 99%